Penerapan Etika Politik Rasulullah dalam Tinjauan Etika Politik Islam Masa Kini - Ernawati Ernawati; Syamsinar Bahar; Kurniati Kurniati (Jurnal Budi Pekerti Agama Islam, 2024)
This article discusses the application of the Prophet's political ethics in reviewing contemporary Islamic political ethics. Islamic political ethics can be seen in several aspects, such as the appointment of leaders, ethics in dealing with rebels, the choice of forms and systems of government, attitudes as politicians, and other issues related to government. Islamic political ethics is always guided by Divine revelation in the form of the Koran and hadith, so that when a leader makes a political decision, he is immediately held accountable before God. Political ethics in Islam includes two things: (1) as a moral philosophy that concerns the political aspects of human life (legitimacy of political power); (2) political ethics refers to behavior when carrying out political activities (political moral aspects), such as chivalry, elegance, politeness, and carrying out duties. The role of political ethics in society is to provide theoretical tools to question and explain political legitimacy in a responsible, rational, objective and argumentative manner. Political ethics is a question of political reality in early Islamic society and how it happened. This is a matter of how society views people who have great power. Islamic politics can also be interpreted as the political activities of some Muslims who use Islam as a standard of values and a basis for group solidarity. Political ethics contains two meanings, namely as a moral philosophy which concerns the political aspects of human life (legitimacy of political power) and political ethics which refers to behavior when carrying out political activities (moral aspects of politics), such as chivalry, elegance, politeness, and carrying out duties. The role of political ethics in society is limited to providing theoretical tools to question and explain political legitimacy in a responsible, rational, objective and argumentative manner, not based on emotions, prejudices and a priori. The task of political ethics is to objectify the discussion of ideological issues that are not directly related to actual politics.